Liquid and Gaseous Fuel from Waste Plastics by Sequential Pyrolysis and Catalytic Reforming Processes over Indonesian Natural Zeolite Catalysts - Mochamad Syamsiro; Shuo Cheng; Wu Hu; Harwin Saptoadi; Nosal Nugroho Pratama; Wega Trisunaryanti; Kunio Yoshikawa (Diponegoro University, 2014)
In this study, the performance of several differently treated natural zeolites in a sequential pyrolysis and catalytic reforming of plastic materials i.e. polypropylene (PP) and polystyrene (PS) were investigated. The experiments were carried out on two stage reactor using semi-batch system. The samples were degraded at 500°C in the pyrolysis reactor and then reformed at 450°C in the catalytic reformer. The results show that the mordenite-type natural zeolites could be used as efficient catalysts for the conversion of PP and PS into liquid and gaseous fuel. The treatment of natural zeolites in HCl solution showed an increase of the surface area and the Si/Al ratio while nickel impregnation increased the activity of catalyst. As a result, liquid product was reduced while gaseous product was increased. For PP, the fraction of gasoline (C5-C12) increased in the presence of catalysts. Natural zeolite catalysts could also be used to decrease the heavy oil fraction (>C20). The gaseous products were found that propene was dominated in all conditions. For PS, propane and propene were the main components of gases in the presence of nickel impregnated natural zeolite catalyst. Propene was dominated in pyrolysis over natural zeolite catalyst. The high quality of gaseous product can be used as a fuel either for driving gas engines or for dual-fuel diesel engine.